Planning greenway along the abandoned railway in Gwangju City, Korea: key components to successful greenway plan - Bonghyun Jeong; Hye-Cheon Kim (European Regional Science Association (ERSA), 2002)
The term greenway in Korea can identify in the word "green" a network only for pedestrians and non-motorized vehicles mobility. The attention should be focused on the possibility of using greenways as a part of a "slow" mobility plan. The greenway of Gwangju can be seen an example of an important change in the Korean urban and transport planning that can use networks for "slow" mobility as one of the most important element for a higher quality level of life. With these considerations in mind this study deals with planning greenways along abandoned rail lines for sustainable community in Gwangju city, Korea. This is aimed at suggesting policy strategies and future directions for constructing greenways along abandoned rail lines of 11km in Gwangju city, Korea. This paper consists of three main sections: concepts of greenways; rail system and transport problems in Gwangju; strategies and directions for constructing greenways in Gwangju. This paper is mainly based on a review of current research reports/papers and an analysis of secondary data.
Keywords: 330